Introduction: towards an ethnography of meeting. (16th March 2017) - Brown, Hannah; Reed, Adam; Yarrow, Thomas
Abstract : This introductory essay describes a novel approach to meetings in relation to broader literatures within and beyond anthropology. We suggest that notwithstanding many accounts in which meetings figure, little attention has been given to the mundane forms through which these work. Seeking to develop a distinctively ethnographic focus to these quotidian and ubiquitous procedures, we outline an approach that moves attention beyond a narrow concern with just their meaning and content. We highlight some of the innovative strands that develop from this approach, describing how the negotiation of relationships 'within' meetings is germane to the organization of 'external' contexts, including in relation to time, space, organizational structure, and society. The essay offers a set of provocations for rethinking approaches to bureaucracy, organizational process, and ethos through the ethnographic lens of meeting.